Development of Android-Based Augmented Reality 3D Card Media for Elementary School Students - Listyana Kumala Sita Nanda; Trisniawati Trisniawati; Mahmudah Titi Muanifah (AlphaMath : Journal of Mathematics Education, 2022)
This study aims to develop an Android based Augmented Reality 3D Card Media on solid figures materials for the grade VI elementary school student, to describe the feasibility and the student responses on Android based Augmented Reality 3D Card Media on solid figures materials for the grade VI elementary school student. This study were Research and Development (R&D) with reference to the Borg & Gall model and which is modified into 7 steps, there are (1) research and initial information collection, (2) planning, (3) initial product development, (4) initial trial, (5) revision I, (6) field trials, (7) revision II. The initial trials is a validation of media experts and material experts. The field trials consisted of teacher trials and small group trials on 6 students in grade VI of SD Negeri 1 Gondangsari. The instrument data that were used to collect data were interview guides and questionnaires. The study results showed that the Android based Augmented Reality 3D Card Media consisted of ARB (Augmented Reality Bangun Ruang) application and the card as a marker and completed with a guidebook to facilitate the user. This Android based Augmented Reality 3D Card Media on solid figures materials meet the feasibility criteria as evidenced by the percentage score of the validation results form media experts 78,66%, material expert validation 85,33%, the teacher trials 90,66%, and the small group trials 94,22% accompanied by positive responses from the students. Therefore, the Android based Augmented Reality 3D Card Media on solid figures materials feasible used as alternative media on mathematics learning at pandemic COVID-19 era for the grade VI elementary school students to help learning everywhere and anytime by maximizing the technological developments.